Keanekaragaman Dung Beetle Di Taman Nasional Bukit Barisan Selatan dan Bufferzone Lampung, Indonesia - Bainah Sari Dewi; Shafa Fauzia Ranti; Candra Yoga Aditama; Rusita Rusita; Sugeng P Harianto (Journal of People, Forest and Environment, 2023)
Dung beetle s live and develop in animal droppings and have a role as second-level seed dispersers. The aim of this research is to determine the level of diversity of beetles found in Taman Nasional Bukit Barisan Selatan. The observation locations were carried out in three locations, namely rice fields dan rivers who located in Sumber Agung village, Suoh, Lampung Barat. This research used the Pit fall trap method or trap traps baited with goat and cow feces. because it is easy to get in the Suoh area and traps are installed in two places, namely rice fields and rivers. The diversity index value of dung beetle s in both habitats is included in the medium diversity category because it is in the diversity value interval: 1 ≤ H' ≤ 3 with the value of H' in rice fields = 1.24 and in rivers = 1.04. Species diversity is classified as moderate because there are not many species occupying the area and the individuals occupying the habitat are unique. Moderate species diversity indicates sufficient productivity and fairly balanced ecosystem conditions with moderate ecological pressure.